Innovation In Banyuwangi Papring Batik In Efforts To Boost The Community’s Economy - Ratna Wijayanti Daniar PARAMITA; Noviansyah RIZAL; Riza Bahtiar SULISTYAN; Danang Wikan CARITO; Ikhwanul HAKIM; Fadhel Akhmad HIZHAM (International Journal of Environmental, Sustainability, and Social Science, 2022)
Batik is one of the characteristics of Indonesia as a form of cultural heritage. Batik has developed and has given birth to various types and patterns of batik that are unique to each region. Batik has become the main focus of several researchers in recent years. One area that continues to strive to preserve its regional culture is in Kampoeng Batara, Papring Environment, Banyuwangi. The purpose of this research is to improve the economy of the Papring Banyuwangi environmental community through training and mentoring of typical Batik Papring Banyuwangi. The method used is a qualitative approach. Data were obtained from interviews with 15 trainees. The indicators used are knowledge, understanding, stamping skills, coloring skills, and creativity. The results show that there is an increase in the economy of the Banyuwangi Papring community through training and mentoring of typical Batik Papring Banyuwangi. The high public interest in batik production is indicated by an increase in sales within 1 month of more than 100 pieces. In addition, the form of improving the ability of the community participating in batik training has been achieved from the results of the assessment before and after the training. Efforts to preserve Banyuwangi culture through batik have been achieved and are able to improve the mindset of the community to continue to preserve their culture.